Inotodiol From Inonotus obliquus Chaga Mushroom Induces Atypical Maturation in Dendritic Cells - Maza, Perry Ayn Mayson A.; Lee, Ji-Hyun; Kim, Yong-Su; Sun, Gyu-Min; Sung, Youn-Joo; Ponomarenko, Ludmila P.; Stonik, Valentine A.; Ryu, Minsook; Kwak, Jong-Young (Frontiers in Immunology, 2021)
Dendritic cells (DCs) have the ability to stimulate naïve T cells that coordinate subsequent adaptive response toward an inflammatory response or tolerance depending on the DC differentiation level. Inotodiol, a lanostane triterpenoid found in Inonotus obliquus (wild Chaga mushroom), is a natural compound with a wide range of biological activities. In this study, we investigated whether inotodiol promotes the maturation of bone marrow-derived DCs (BMDCs) and inotodiol-treated BMDCs induce T cell activation. Inotodiol increased the expression of surface maturation markers, including MHC-II, CD86, and CD40, on BMDCs without affecting the production of various cytokines, including TNF-α and IL-12p40 in these cells. T cells primed with inotodiol-treated BMDCs proliferated and produced IL-2, without producing other cytokines, including IL-12p40 and IFN-γ. The phosphatidylinositol-3-kinase inhibitor wortmannin abrogated the upregulation of Akt phosphorylation and CD86 and MHC-II expression induced by inotodiol. However, inotodiol failed to induce phosphorylation of the IκB kinase and degradation of IκB-α, and increased expression of CD86 induced by inotodiol was not blocked by an IκB kinase inhibitor. These results suggest that inotodiol induces a characteristic type of maturation in DCs through phosphatidylinositol-3-kinase activation independent of NF-κB, and inotodiol-treated DCs enhance T cell proliferation and IL-2 secretion.